Factors influencing purchase intention towards luxury counterfeit products – a case study of lecturers and degree students in UiTM Arau, Perlis / Muhammad Aiman Iz’aan Mohd Lee - Mohd Lee, Muhammad Aiman Iz’aan (Universiti Teknologi Mara Perlis, 2020)
The purpose of this study is to determine whether denial of responsibility, denial of injury, denial of victim and appeal to higher loyalties are the variables that influence purchase intention towards luxury counterfeit products. The population used in this study were the lecturers and degree students at Universiti Teknologi Mara Arau, Perlis. Sampling technique used was stratified sampling with a total sample of 341 respondents which is consists of 305 students and 36 lecturers. The data collection used was questionnaire method. Frequency distribution analysis, factor analysis, descriptive analysis, reliability analysis, Pearson’s correlation analysis and regression analysis was used as an analytical technique. Research results show that denial of responsibility, denial of injury, denial of victim and appeal to higher loyalties affect purchase intention towards luxury counterfeit products. All those variables are found to be significant for this study. For future research, the researchers should enlarge the sample size to answer questionnaire at the other universities in Malaysia or public people. It is because the finding will be precise and represent overall population in Malaysia. Larger sample size important as the research can be generalized for the whole study. Similar study must be taken for other samples. Large sample size important because can regulate whether the result is supported or not supported. Finally, In the future research, researcher may conduct the same research with the same dependent variable and independent variables, but they are suggested to include moderator and mediator. This is to identify whether the research is influence by other factors or not. Hence the result will be more accurate.